Constitutional court and constitutional economy: A study on decisions of Indonesian constitutional court - Salman, Radian (UUM COLGIS Universiti Utara Malaysia, 2009)
Indonesian constitutional court has the authority to determine the constitutionality of statutes. This paper focuses on the study on the decisions of the Constitutional court in judicial review cases concerning legal issues of economic system as promulgated in article 33 of the Constitution. Study on the decisions on the cases of electricity law, water law and oil and gas law shows how the Constitutional court take part in economic policy. It is argued that constitutional interpretation of judges upon the question of economy converges at the following issue: the role of state in economic system; the meaning of welfare state; and economic market and interrelation among them. However, in broader perspective, the role of constitutional court raise more general questions about the interrelations of law (constitution) and economics and the role of economic reasoning in judicial review.